THE IMPLEMENTATION OF THE SCHOOL UNITS MANAGEMENT AUTONOMY PROGRAM – PAGUE – IN THE REGIONAL EDUCATION COORDINATION OF TEFÉ - da Costa, Iberson Mendes; Chena, Ana Eugenia Gonzalez (Seven Editora, 2025)
The School Units Management Autonomy Program (PAGUE) is a public policy of financial decentralization implemented in the State of Amazonas. This study analyzes its implementation in the Regional Education Coordination of Tefé (CRET), considering advancements, challenges, and the perceptions of the main actors involved, such as school principals and/or members of the APMCs/School Councils. The program is based on the development of application plans, community approval, and strict accountability procedures. The general objective of the research was to analyze the implementation process of PAGUE, identifying the main challenges faced by state schools in Tefé. The methodology used was a qualitative case study, and data were initially collected through documentary and bibliographic research characterized by an exploratory survey of the available literature. Subsequently, semi-structured interviews were conducted with current school principals, along with a structured questionnaire applied to former principals or APMC members. The participation of the APMCs or School Councils in the decision-making process revealed regional disparities, highlighting the need for greater community engagement and qualification. It is concluded that the success of PAGUE depends on alignment with regional demands, continuous training, and investments in basic and technological infrastructure, and that the program presents significant potential to modernize educational management in Amazonas, promoting greater equity and efficiency in resource allocation.DOI: https://doi.org/10.56238/sevened2025.038-032